A Threefold Assessment of the Romanian Economy’s Eco-efficiency - Viorel Niţă (Romanian Journal of European Affairs)
The present paper assesses the ecological sustainability of the Romanian economy from three different angles. The first two applications use the economy’s energy and material consumption as proxy for its overall environmental impact. The third assessment approach is a qualitative and context-based one: the main obstacles to and opportunities for incorporating sustainability-competitiveness synergies into the Romanian industrial firms’ management are identified. In the period 2000-2007, GDP growth was an important contributor to the Romanian economy’s eco-efficiency levels, while the material and energy consumption remained constant or even increased. The predominance of competitive advantages based on low labour costs, high potential of increasing labour productivity, deficient environmental and industrial policies, and lack of awareness in both business and policy environment as to the beneficial role of resource productivity increase constitute significant obstacles to adopting competitive sustainability strategies. Fortunately, the relatively low levels of eco-efficiency and eco-innovation in industry offer in fact a wide scope of still unexploited win-win solutions. On the basis of the results, further research directions are sketched and several desirable public policy actions for enhancing the ecological sustainability of the Romanian economy are put forward.